2018
DOI: 10.24015/japm.2017.0048
|View full text |Cite
|
Sign up to set email alerts
|

Videolaryngoscopy in Airway Management: What Every Anesthesiologist Should Know!

Abstract: Aim of review:The aim of this article is to convey several hotspot issues regarding the use of videolaryngoscopy (VL) in airway management that anesthesiologists are often concerned. Methods: Recent literature in the past 20 years about the use of VL in the clinical airway management were searched from the Pubmed and Cochrane databases and reviewed, in order to determine the strengths and weakness of VL and conflicting issues regarding the role of VL in airway management. Recent findings: The benefits of VL ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“… 5 , 44 Although a slim designed McGrath MAC X-blade can be used in patients with restricted mouth opening, 45 a very limited mouth opening can make the use of VL impossible, as “an inter-dental distance of at least 18–20 mm is required to insert even the narrow blades”. 46 , 47 Moreover, some pathologic conditions of the upper airway may prevent success with VL. A large retrospective study of patients with predicted difficult airways showed that the strongest predictors of failed VL were “altered neck anatomy with the presence of a surgical scar, radiation changes, or mass”.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 44 Although a slim designed McGrath MAC X-blade can be used in patients with restricted mouth opening, 45 a very limited mouth opening can make the use of VL impossible, as “an inter-dental distance of at least 18–20 mm is required to insert even the narrow blades”. 46 , 47 Moreover, some pathologic conditions of the upper airway may prevent success with VL. A large retrospective study of patients with predicted difficult airways showed that the strongest predictors of failed VL were “altered neck anatomy with the presence of a surgical scar, radiation changes, or mass”.…”
Section: Discussionmentioning
confidence: 99%
“…Successful intubation requires adequate glottic visualisation and subsequent smooth insertion of the ET tube. [ 10 11 ] The current study showed significantly faster total intubation time using the SAM-VL than McGrath MAC ® laryngoscope. To our knowledge, there is no prior study that directly compared the intubation times between the two.…”
Section: Discussionmentioning
confidence: 64%
“…The 120 seconds time-limit set was less than the average time for SpO 2 to decrease to 90% during the apnoea following oxygenation with 80% oxygen during induction. [ 10 ] The attending anaesthesiologist would manage the complications accordingly. Management of hypotension and bradycardia were by giving IV fluid boluses (10 ml/kg body weight of Ringer’s lactate), vasopressors (ephedrine 5-10 mg IV bolus), and atropine (0.5 mg IV) if necessary.…”
Section: Methodsmentioning
confidence: 99%
“…Awake VL has been described in the literature as easier and faster compared to awake FOB[ 13 ] but very limited mouth opening can make the use of VL impossible, as an inter-dental distance of at least 18–20 mm is required to insert even the narrow blades. [ 23 ] Awake VL was not used in the cases studied probably because consultants at our institution feel that conducting, demonstrating, and teaching FOB is more important than awake VL. In the process, they are short of expertise in doing awake VL.…”
Section: Discussionmentioning
confidence: 99%